EFEK MEDIASI KEPUASAN KERJA PADA PENGARUH LINGKUNGAN KERJA DAN TUNJANGAN PERBAIKAN PENGHASILAN TERHADAP KINERJA PEGAWAI INSPEKTORAT KABUPATEN PONOROGO - Wibowo, Bayu Aji; Suseno, Y. Djoko; Sutarno, Sutarno (Universitas Slamet Riyadi, 2019)
Aims to understand research significant influence between: (1) work environment to work satisfaction, (2) officials will have their income to work satisfaction, (3) work environment against the employee performance, (4) officials will have their income to the performance of, (5) satisfaction on the performance of work, (6) the effect of mediation work satisfaction to the influence of the performance of work environment, (7) the effect of mediation work satisfaction to the influence of officials will have their income to the employee performance kabupaten ponorogo inspektorat. The population is employees inspektorat kabupaten ponorogo in 2019 at a number of 35 people. Sample taken by using the sampling method of saturated, where all of an officer at the inspektorat kabupaten ponorogo which consisted of 35 employees used as a subject in this research. The technique of the collection of data using the practical and watchful such through reliability. Linear regression analysis using techniques and the worship of idols with classical test, the analysis, f and test test the coefficient of determination. The results of the study conclusion: (1) work environment significant impact on work satisfaction, (2) officials will have their income significant impact on work satisfaction, (3) officials will have significant impact on the performance of income, (4) work satisfaction significant impact on the performance of, (5) work environment has no significant impact on the performance of, (6) satisfaction mediate environmental influences on the performance of work, (7) satisfaction will have their working hours are not mediate the influence of income to the employee performance kabupaten ponorogo inspektorat.